Relationship between initial probing depth and residual pockets following mechanical periodontal treatment - KURU, LEYLA (AVES PRESS LTD, 2015)
Objective: The aim of this study was to evaluate the relationship between initial probing depth (IPD) and the ratio of residual periodontal pocket in chronic periodontitis patients following mechanical periodontal therapy (MPT). Methods: A total of 1102 periodontal pockets with IPD 4-9 mm (both included) in 11 chronic periodontitis (CP) patients were included and grouped according to their IPDs and number of roots (single-/mult-irooted). MPT consisting of oral hygiene instruction, scaling and root planing was applied in 2 sessions with one-week interval. Plaque index, gingival index, probing depth (PD), clinical attachment levels and bleeding on probing (BoP) were measured before and 8 weeks after MPT. Following MPT, periodontal pockets demonstrating PD >= 5 mm and BoP (+) were defined as residual periodontal pockets. Results: Our results showed that 10.89% of the sites from single-rooted teeth and 26.59% of the sites from multi-rooted teeth were remained as residual periodontal pockets. Further, positive correlations were found between IPD and residual periodontal pocket ratio for both single-and multi-rooted teeth (p<0.001). Conclusion: Within limitations of this study, our results suggest that applied treatment had improved the periodontal parameters and the periodontal pockets of multi-rooted teeth in CP patients remained as residual pockets in a high percentage and the deeper IPD the higher probability of residual pockets.
Keywords: Dental scaling; root planing; periodontal pocket